Mutations in the anti-sigma H factor RshA confer resistance to econazole and clotrimazole in Mycobacterium smegmatis - Morbidoni, Héctor Ricardo (2019)
Azole drugs such as econazole, are active on Mycobacterium tuberculosis and Mycobacterium smegmatis; however, the identification of their target(s) is still pending. It has been reported that mutations in the non-essential system mmpL5-mmpS5 conferred resistance to econazole in M. tuberculosis. We herein report that an azole-resistant mutant screen in M. smegmatis rendered mutations in rshA, encoding a non-essential anti-sigma H protein.